Childhood and youth literature in the digital age: towards effective mediation strategies Scoping review according to the PRISMA method - CHENNOUFI, Ismail; RIZK, Khalid (Revue Internationale du Chercheur, 2025)
Abstract The text is part of a line of studies listing theoretical or empirical work in the field of children's and youth literature. It comes from a literature review of 464 articles published between 2010 and 2024 in the main international peer-reviewed journals, on children's and youth literature in the digital age, particularly the question of mediation. To select the relevant references for our research, we followed and respected the PRISMA protocol. The analysis of these selected references was carried out using Vosviewer and Nvivo. The results obtained allowed us to identify the “Knowledge gap” research gap, namely the mechanisms for effective mediation carried out by the various stakeholders, with children and young people, in particular the educational mediation of teachers, parental monitoring and the mediation of librarians and publishers.